Design, Synthesis, and Evaluation of New P2Y2 Receptor Antagonists and Fluorescent Ligands - Knight, Rebecca (2025)
The P2Y2 receptor (P2Y2R) is an exciting therapeutic target for numerous diseases including atherosclerosis, idiopathic pulmonary fibrosis, and cancer. Despite this, there are a limited number of receptor antagonists available, none of which are clinically viable. The highest affinity P2Y2R antagonists detailed are AR-C118925 and its thiazole-based analogues, for which physiochemical properties remain a barrier for future drug development.